2005
DOI: 10.1515/hf.2005.035
|View full text |Cite
|
Sign up to set email alerts
|

Detection of failures of adhesively bonded joints using the acoustic emission method

Abstract: Wooden glued constructions require touch-free monitoring of destructive processes, especially in adhesive bonds that are most exposed to failure. The objective of the investigations was to describe failure processes in the adhesive bond of wood joints, in particular to determine their initiation, propagation, and destruction. The acoustic emission (AE) method was employed as the carrier of information about changes occurring in glued joints, whereas the numerical method was applied to determine values of distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…For plywood type 3, even though its specimens have the same physical dimension as the solid wood specimens, only half the AE activity of that for solid wood was measured. Besides the fact that glued wooden structures generally generate a lower number of AE events than solid wood (Gozdecki and Smardzewski 2005), the intrinsic pre-damage due to industrial production of plywood is also of relevance. In particular, lathe checks have already led to a prior release of the material's elastic energy during veneer processing.…”
Section: Acoustic Emission Activity and Knee-point Evaluationmentioning
confidence: 99%
“…For plywood type 3, even though its specimens have the same physical dimension as the solid wood specimens, only half the AE activity of that for solid wood was measured. Besides the fact that glued wooden structures generally generate a lower number of AE events than solid wood (Gozdecki and Smardzewski 2005), the intrinsic pre-damage due to industrial production of plywood is also of relevance. In particular, lathe checks have already led to a prior release of the material's elastic energy during veneer processing.…”
Section: Acoustic Emission Activity and Knee-point Evaluationmentioning
confidence: 99%
“…The main difference between AE sensing and other non-destructive methods is the capability to inspect in real time, since continuous monitoring in situ can be carried out, and the onset and progression of damage to a structure can be assessed, even when this is not possible by means of visual inspection. Some applications of the AE method to the study of wood behavior can be found in [ 21 , 22 , 23 , 24 , 25 , 26 ], dealing with detection of failure in adhesive joints and evaluation of fractures and its propagation in wood.…”
Section: Introductionmentioning
confidence: 99%